Establishing cephalometric norms of upper and lower lips to Rickett’s E-line in the Malay female population of Kuantan city: a pilot study - Sivagnanam, Mangaiyarkarasi; Cheong, Joo Ming (IIUM Press, International Islamic University Malaysia, 2023)
The purpose of the study was to determine the cephalometric norms of upper and lower lips to the Rickett’s E-line in the Malay female population of Kuantan city, and to compare it with the Caucasian norms. This was a retrospective study involving 40 pre-existing lateral cephalometric radiographs taken from October 2017 to October 2021 of skeletal Class I females of pure Malay ethnic group aged 20 to 40 retrieved from two private dental clinics in Kuantan city of Pahang state, Malaysia (Dr Fatain’s Dental Clinic Taman Tas; Dr Fatain’s Dental Clinic Indera Mahkota 3). These radiographs were hand traced using acetate paper and 0.3 mm leaded propelling pencil on a light view box in a darkened room. The soft tissue outlines and the Rickett’s E-line (from the tip of the nose to the soft tissue chin) were drawn and the distance of the upper and lower lips to this line was measured in mm with a metal ruler. The values were compared with the Caucasian norms [upper lip to E-line: -4 mm; lower lip to E-line: -2 mm (± 2)]. The cephalometric norms of upper and lower lips to the E-line among the Malay females of Kuantan city were -1.3 mm (± 2.0) and 0.19 mm (± 1.9) respectively. This value was significantly different than the norms of the Caucasian population (p < 0.001). In conclusion, the cephalometric norms of upper and lower lips to Rickett’s E-line in the Malay female population of Kuantan city were established: upper lip -1.3 mm (± 2.0) and lower lip 0.19 mm (± 1.9), which were found to be more protrusive than the Caucasian norms.